RNA binding activity of the recessive parkinsonism protein DJ-1 supports involvement in multiple cellular pathways - van der Brug, Marcel P. (National Academy of Sciences, 2008)
Parkinson's disease (PD) is a major neurodegenerative condition with several rare Mendelian forms. Oxidative stress and mitochondrial function have been implicated in the pathogenesis of PD but the molecular mechanisms involved in the degeneration of neurons remain unclear. DJ-1 mutations are one cause of recessive parkinsonism, but this gene is also reported to be involved in cancer by promoting Ras signaling and suppressing PTEN-induced apoptosis. The specific function of DJ-1 is unknown, although it is responsive to oxidative stress and may play a role in the maintenance of mitochondria. Here, we show, using four independent methods, that DJ-1 associates with RNA targets in cells and the brain, including mitochondrial genes, genes involved in glutathione metabolism, and members of the PTEN/PI3K cascade. Pathogenic recessive mutants are deficient in this activity. We show that DJ-1 is sufficient for RNA binding at nanomolar concentrations. Further, we show that DJ-1 binds RNA but dissociates after oxidative stress. These data implicate a single mechanism for the pleiotropic effects of DJ-1 in different model systems, namely that the protein binds multiple RNA targets in an oxidation-dependent manner.